Mesoporous MgO enriched in Lewis base sites as effective catalysts for efficient CO2 capture. (15th April 2023) - Wang, Lei; Yao, Yi; Tran, Trinh; Lira, Patrick; Sternberg P.E., Steven; Davis, Richard; Sun, Zhao; Lai, Qinghua; Toan, Sam; Luo, Jianmin; Huang, Yudai; Hu, Yun Hang; et al.
Abstract: Capturing CO2 has become increasingly important. However, wide industrial applications of conventional CO2 capture technologies are limited by their slow CO2 sorption and desorption kinetics. Accordingly, this research is designed to overcome the challenge by synthesizing mesoporous MgO nanoparticles (MgO-NPs) with a new method that uses PEG 1500 as a soft template. MgO surface structure is nonstoichiometric due to its distinctive shape; the abundant Lewis base sites provided by oxygen vacancies promote CO2 capture. Adding 2 wt % MgO-NPs to 20 wt % monoethanolamine (MEA) can increase the breakthrough time (the time with 90% CO2 capturing efficiency) by ∼3000% and can increase the CO2 absorption capacity within the breakthrough time by ∼3660%. The data suggest that MgO-NPs can accelerate the rate and increase CO2 desorption capacity by up to ∼8740% and ∼2290% at 90 °C, respectively. Also, the excellent stability of the system within 50 cycles is verified. These findings demonstrate a new strategy to innovate MEA absorbents currently widely used in commercial post-combustion CO2 capture plants. Highlights: Mesoporous nano-MgO with abundant oxygen vacancies improved the breakthrough time. MgO nanoparticles improved CO2 absorption & desorption rate. Higher amount of absorbed & desorbed CO2 and excellent recyclability.